Prevalence of diabetic retinopathy and its associated factors among adults in East African countries: A systematic review and meta-analysis - Habtamu Wagnew Abuhay; Tigabu Kidie Tesfie; Meron Asmamaw Alemayehu; Muluken Chanie Agimas; Getaneh Awoke Yismaw; Gebrie Getu Alemu; Nebiyu Mekonnen Derseh; Bantie Getnet Yirsaw (PLoS ONE, 2025)
Introduction Diabetes mellitus (DM) is one of the most significant public health problems. Globally, one in ten adults has diabetes, and it results in macro- or microvascular complications, such as diabetic retinopathy (DR). It is one of the most prevalent eye complications associated with DM, and it is the main cause of vision loss. Even though East African countries face a growing burden of diabetes and DR, no study depicts the regional prevalence and its associated factors. Therefore, this study aimed to estimate the pooled prevalence of DR and its associated factors among adults in East African countries. Methods We extensively searched PubMed, Embase, Scopus, Google Scholar, and Google for relevant studies. A forest plot was used to estimate the pooled prevalence of diabetic retinopathy using DerSimonian and Laird’s random-effects model. We checked publication bias using funnel plots and Egger’s regression test. Potential heterogeneity was tested using the I-squared statistic. Subgroup analysis, sensitivity analysis, and meta-regression analysis were also performed. Furthermore, the pooled odds ratios for the associated factors were estimated. The research protocol was registered in PROSPER. Results Among the 29 included studies, the estimated pooled prevalence of DR in East African countries was 28% (95% CI 23.0, 33.0). Besides, age ≥60 (OR = 2.88, 95% CI: 1.55, 5.32), body mass index ≥ 25 (AOR = 2.85; 95% CI: 1.69, 4.81; I2 = 85.4%, p < 0.001), and hemoglobin A1c levels ≥7 (OR = 2.48, 95% CI: 1.46, 4.23) were significantly associated with the prevalence of DR. Conclusions The prevalence of DR in East Africa was high, with more than one in four individuals with diabetes developing DR. Besides, advanced age, higher body mass index, and elevated hemoglobin A1c levels were significant factors associated with increased DR prevalence. Therefore, comprehensive diabetes management focusing on optimal glycemic control and healthy weight maintenance is essential to mitigate the problems. Also, the Ministries of Health and policymakers should prioritize and implement targeted strategies to address the identified modifiable risk factors, aiming to reduce the prevalence of DR in the region. Trial registration Systematic review registration: PROSPERO (2024: ID = CRD42024511437). https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024511437.